Geofluids Assessment of the Ayub and Shafa Hot Springs in Kopet-Dagh Zone (NE Iran): An Isotopic Geochemistry Approach - Hossein Mohammadzadeh; Majid Kazemi (Geofluids)
Geothermal energy has a wide range of uses in our life. It is very important to characterize the temperature and the depth of geothermal reservoirs. The aim of this paper is the determination of type, origin source of water temperature, and depth of water circulation in the Ayub-Peighambar and Shafa (AP and SH) hot springs, located in NE Iran, using hydrogeochemistry and environmental isotopes (2H and 18O). AP hot spring has elevated temperature (36–40°C) and as such is very important for balneotherapy and geotourism industry purposes. The average values of δ18O and δ2H for this hot spring (−10‰ and −73‰, resp.) are analogous to that of geothermal and meteoric waters. This indicates that the heat source cannot be related to volcanic activities (with average δ18O value of about 5‰) and it is most probably associated with geothermal gradient with deep circulation of groundwater through faults. Based on Na-K geothermometers coupled with isotopic (18O and 2H) geochemistry the temperature of the AP geothermal reservoir was estimated to be in the range of 100–150°C with 3–5 and 4.2 kilometres’ depth, respectively. Chemically, the AP samples are CaSO4 facies with a chemically homogeneous source and steam heated waters type.